L1 transfer in article selection for generic reference by Spanish, Turkish and Japanese L2 learners - Snape, Neal; García Mayo, María del Pilar; Gürel, Ayşe (International Journal of English Studies, 2013)
This study examines second language (L2) acquisition of English generic noun phrases (NPs) by Spanish, Turkish and Japanese learners. The aim is to identify the role of the first language (L1) in the L2 acquisition of definite NP-level generics and indefinite sentence-level generics with singular, bare plural, and mass generic nouns. The four languages in this study differ in the way they express generic interpretations: English and Spanish have article systems, Turkish has an indefinite article, but no definite article, and Japanese lacks an article system. Advanced and upper intermediate L2 learners were tested via a forced choice elicitation task. The results reveal different patterns of article selection across the three groups of L2 learners, which correspond with L1 transfer effects. Our findings suggest that L2 article choice is largely determined by the way the L1 realizes generic reference.